The promise of biological markers for treatment response in first-episode psychosis: a systematic review - Fond, Guillaume; Leweke, F. Markus; Meyer-Lindenberg, Andreas (Schizophrenia bulletin, 2015)
Successful treatment of first-episode psychosis is one of the major factors that impacts long-term prognosis. Currently, there are no satisfactory biological markers (biomarkers) to predict which patients with a first-episode psychosis will respond to which treatment. In addition, a non-negligible rate of patients does not respond to any treatment or may develop side effects that affect adherence to the treatments as well as negatively impact physical health. Thus, there clearly is a pressing need for defining biomarkers that may be helpful to predict response to treatment and sensitivity to side effects in first-episode psychosis. The present systematic review provides (1) trials that assessed biological markers associated with antipsychotic response or side effects in first-episode psychosis and (2) potential biomarkers associated with biological disturbances that may guide the choice of conventional treatments or the prescription of innovative treatments. Trials including first-episode psychoses are few in number. Most of the available data focused on pharmacogenetics markers with so far only preliminary results. To date, these studies yielded - beside markers for metabolism of antipsychotics - no or only a few biomarkers for response or side effects, none of which have been implemented in daily clinical practice. Other biomarkers exploring immunoinflammatory, oxidative, and hormonal disturbances emerged as biomarkers of first-episode psychoses in the last decades, and some of them have been associated with treatment response. In addition to pharmacogenetics, further efforts should focus on the association of emergent biomarkers with conventional treatments or with innovative therapies efficacy, where some preliminary data suggest promising results.
Gesehen am 30.11.2017